2013
DOI: 10.1142/s1793431113500061
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Behavior of Steel Monorail Bridges Under Train Load During Strong Earthquakes

Abstract: This paper investigated dynamic responses of steel monorail bridges incorporating train-bridge interaction under strong earthquakes. Two types of steel monorail bridges were considered in the study: a conventional type with steel track-girder; an advanced type with composite track-girder and simplified lateral bracing system. During strong earthquakes, monorail train was assumed standing on the track-girder of monorail bridges. Observations through the analytical study showed that considering the monorail trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The analyses demonstrated that the dynamic train system acts as a damper on the bridge, and thus considering the train as an additional mass is a conservative approach. Another later research [11] analytically investigating the effect of train dynamics on seismic response of steel monorail bridges under strong earthquakes conducted by Kim et al revealed that modeling the monorail train as an additional mass rather than a dynamic system overestimates the effect of train load on the bridge seismic response. A similar study, this time on the heavy vehicle effect on the dynamic behavior of a highway viaduct under moderate ground motions, has been carried out by Kim et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses demonstrated that the dynamic train system acts as a damper on the bridge, and thus considering the train as an additional mass is a conservative approach. Another later research [11] analytically investigating the effect of train dynamics on seismic response of steel monorail bridges under strong earthquakes conducted by Kim et al revealed that modeling the monorail train as an additional mass rather than a dynamic system overestimates the effect of train load on the bridge seismic response. A similar study, this time on the heavy vehicle effect on the dynamic behavior of a highway viaduct under moderate ground motions, has been carried out by Kim et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…(8), q denotes the linear density of the beam; N denotes the shape function of the element which is derived from Eqs. (1) to (6).…”
Section: Straddle-type Monorail Track Beam Systemmentioning
confidence: 99%
“…Trahair [5] proposed a calculation method which takes the beneficial lateral load into account in the analysis of the lateral buckling of the monorail steel beam. Kim and Kawatani [6] analyzed the dynamic responses of the improved monorail steel track beam with a transverse support system under seismic activities. Ren et al [7,8], Zhao [9], Du and Wang [10], Ma [13], Liu [11,12] and Shan [14] also studied the responses of the straddle monorail vehicle from different aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Naeimi et al used finite element method and dynamic simulation to study the deformation of track beam under compression, the coupling dynamic response of vehiclebridge under the condition of elastic beam is calculated, and the correctness of the model is verified by comparing the dynamic simulation results of tires with those of vehicle manufacturers [11]; Lv, KK et al studied the influence of wheel eccentricity on the vertical vibration of the suspended monorail vehicle through experiments and simulations, and determined that the abnormal vibration of the body was mainly caused by the wheel eccentricity [12]; Kim. CW et al studied the dynamic response of steel beams under strong earthquakes with consideration of vehicle-bridge interaction, and the aseismic behavior of monorail rail beam with steel structure is affirmed [13].…”
Section: Introductionmentioning
confidence: 99%